Diagnostic Images of the Ocular Fundus Using a Low-Cost Portable Endoscope in Premature Patients at Risk of Developing Retinopathy of Prematurity - Luz Consuelo Zepeda-Romero; Jose Alfonso Gutierrez Padilla; Daniel Perez-Rulfo Ibarra; Jaime Orozco-Perez; Rodrigo Alonso Delgadillo; Lilia Paulina Rodríguez; Guillermo Yanowsky-Reyes (Journal of Ophthalmology)
The purpose of this article is to describe how fundus images are obtained using a low-cost device: the “Visual Ear Wax Cleaner Tool” portable endoscope (Soonhua Inc., China) connected to a smartphone, after installation of free applications (“Inskam” and “CameraFI”) using the smartphone screen as a monitor and after medication mydriasis, local anesthesia, and blepharostat placement. With this endoscope, video recording and fundus imaging are easily performed, for the case of patients at the risk of developing retinopathy of prematurity (ROP), facilitating timely screening in order to start treatment in patients who require it. This fundus imaging technique shares certain similarities with the RetCam® (Clarity, Pleasaton California) system, which performs real-time fundus imaging providing the ability to record and document findings and capture images from the video footage, with high quality and definition, although with a smaller angle of vision. The capture of images using a smartphone allows storing and sharing the images. These are devices which are generally accessible and portable and which use simplified energy sources, requiring very simple training. The low-cost, easy-to-learn technique and quick sharing of images through communication networks make this a tool to be considered for the practice of telemedicine.